An investigation into the use of a nature reserve as a cross-curricular teaching resource - Luckhoff, Augusta Henrietta (Rhodes University, Faculty of Education, Department of Education, 1996)
This study documents the development of the Queenstown nature reserve as a cross-curricular tea~hing resource. Participants in the project included the researcher, the municipality nature conservation officer and the senior Geography and Biology teachers from five high schools in the town. A modified action research approach was adopted. Data was collected from workshops and interviews and then analyzed. The conclusion of the research was that the participants perceived that the project had been worthwhile and was to be continued. The nature reserve is now more widely and usefully used
Keywords: Environmental education -- South Africa; National parks and reserves -- South Africa